2019
DOI: 10.1088/1742-6596/1295/1/012067
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Rice Straw Weight Fraction and Particle Size on Thermal Conductivity and Mechanical Properties of Polypropylene Composite

Abstract: Polypropylene is a widely used material for various types of equipment. As a recyclable thermoplastic polymer, polypropylene composite provides an attractive quality of thermal insulation due to its heat-retaining property. The use of rice straw for filler in thermal insulating material is based on its low thermal conductivity, renewable material, and low cost production techniques. The composite were manufactured by melt-mixing of neat polypropylene and filler of various weight fractions, pellet formation, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
2
1
0
Order By: Relevance
“…In conclusion to the results obtained in compression and bending tests it becomes clearer that the elastic modulus in bending and compression increases with decreasing miscanthus particle size by creating better interfacial bending [30] with chitosan matrix. These results are in agreement with those obtained for rice straw/ polypropylene composite [44] where authors found a decrease in strength of PP composites as the particle size increases (20 MPa for 18-35 mesh straw and 15.6 MPa for 325 mesh straw) and wood/PP where a clear increase of 50% in strength and 23% of rigidity is obtained for smaller particle size (0.25 mm) in comparison to higher one (0.42 mm) [30]. However, to understand more clearly about the size effect of miscanthus fibres on the different properties of the chitosan-based composites, SEM analysis were performed on the surface of Mm and Ms fibres.…”
Section: Bending Propertiessupporting
confidence: 92%
“…In conclusion to the results obtained in compression and bending tests it becomes clearer that the elastic modulus in bending and compression increases with decreasing miscanthus particle size by creating better interfacial bending [30] with chitosan matrix. These results are in agreement with those obtained for rice straw/ polypropylene composite [44] where authors found a decrease in strength of PP composites as the particle size increases (20 MPa for 18-35 mesh straw and 15.6 MPa for 325 mesh straw) and wood/PP where a clear increase of 50% in strength and 23% of rigidity is obtained for smaller particle size (0.25 mm) in comparison to higher one (0.42 mm) [30]. However, to understand more clearly about the size effect of miscanthus fibres on the different properties of the chitosan-based composites, SEM analysis were performed on the surface of Mm and Ms fibres.…”
Section: Bending Propertiessupporting
confidence: 92%
“…The cumulative effect of treated yam peel at 8 wt.% addition may give rise to the most significant thermal conductivity improvement observed at that weight percent as compared to others samples [ 65 ]. This property significantly increases in YPP for both treated and untreated CY/YPP composites it substantiates the research work of [ 66 ] that noted reduced thermal conductivity of polypropylene with increasing particulate rice straw. Treatment of fibres reduces the diameter of fibres which caused increased aspect ratio.…”
Section: Resultssupporting
confidence: 89%
“…Jiang et al 37) in 2018 used modification of rice straw by in situ polymerization of ammonium polyphosphate (APP) polyelectrolyte.This modification helped grafting of ammonium polyphosphate into the rice straw surface Composite were made from HDPE and modified rice straw and flame retardancy of the following composite made was compared .A char layer was formed on composite during flame test ,This formed layer has more thermal stability hence it improved the retardancy test.Zandi et al 38) in 2019 worked on rice straw by chemically reacting and alkali pulping and benzylation reactions the inter and intramolecular hydrogen bonding got destroyed,also the cellulose part of the rice husk got separated from the lignin part. Two outputs were obtained such as benzylated pulp (BP) and pulping liquor (PL) rich in cellulose both were mixed with PLA (polylactic acid ).The composite made were done for soil biodegradation test ,on PLA sheets as well as PLA biocomposite ,in final result degradation occurrence were seen in biocomposites.Wahyuni et al 39) prepared composites with polypropylene (PP) and rice straw as filler in it PP gives a great property in heat retention .The composite were made by melt mixing and neat polypropylene and were put into various fractions .In this paper various research was mainly done on finding the effects of weight fraction,There sizes and pretreatment on their thermal conductivity .Composite made from fine particles gave lower thermal conductivity and much more of tensile strength as compared to that of coarse particles. Inayati et al 40) in 2019 used rice straw along with chitosan and plasticizer as additives to the bioplastic being researched Glycerol was being added to it as a plasticizer and with variation upto 25, 30, 35 %.Made composite were later experimented by water swelling, oil Swelling, UTM and FTIR were performed on the composite .In result it was found that more the glycerol was added more was the water swelling but less in the case of oil swelling test .Jamaludinand Bahari 41) worked on rice straw and bagasse in preparation of binderless particleboard (BPB).Two ratio 50:50 and 40:60 ,MOE (Modulus of elasticity),MOR (Modulus of rupture) , Internal Bonding, water absorption and thickness swelling properties were determined and compared .Bagasse alone gave better values of the tested result and rice straw gave the minimum value of MOR,MOE and IB values .In this research it was also found that if rice was more than 3 months then is becomes brittle hence it properties were changed so it must be used in fresh form.…”
Section: Fig 5: Characteristics Of Natural Compositementioning
confidence: 99%